Tajam Penglihatan Pasca Operasi Fakoemulsifikasi Pada Pasien Katarak Senilis Dengan Dan Tanpa Diabetes Melitus Dan Hipertensi - Yuliana Nur Halimah; Yulia Wardany (Fakultas Kedokteran Universitas Riau, 2026)
The most common cataract surgery technique is phacoemulsification. The presence of systemic comorbidities can be a perioperative complicating factor and increase the risk of complications and affect postoperative visual acuity. The purpose of this study was to determine the visual acuity after phacoemulsification in senile cataract patients with and without diabetes mellitus and hypertension. This study used a cross-sectional analytic observational method with a sample size of 232 patients. Data were taken from medical record using total sampling. Visual acuity after phacoemulsification in the category of good vision (better or equal to 0.48 logMAR) and poor vision (worse than 0.48 logMAR) both without correction (UCVA) and with correction (BCVA). Data were analyzed statistically with SPSS. There was a statistically significant improvement in visual acuity after phacoemulsification across all groups, including cataract patients without diabetes mellitus and hypertension (p